An analysis of the Saltukname in its fifteenth century context - Aydoğan, Zeynep. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This thesis examines the Saltukname, the legendary account of the life and deeds of the thirteenth-century dervish-warrior Sarı Saltuk. While stories about Sarı Saltuk seem to have circulated in gazi-dervish circles of the Balkans since at least the late thirteenth century, the text we have at hand was compiled by Ebu'l-Hayr Rumi, a member of Prince Cem's court, who spent some seven years in the Balkans collecting the oral traditions before he submitted the final written version to Cem circa 1480. In this study, the resulting text is analyzed not simply as the accumulation of centuries-old oral traditions that reflected the worldview of frontiersmen, but also as an authored, or at least heavily edited, text that also voiced the concerns of a certain segment of the Ottoman court that was receptive to these circles in the late fifteenth century. With this dual aim in mind, the political and ideological strands embedded within the text are grounded in the Ottoman political context of the late fifteenth century. More specifically, Chapter One outlines first the thirteenth-century context in which the historical Saltuk lived and then the fifteenth-century context in which the text itself was compiled. The remaining chapters focus on and try to contextualize selected aspects of the text. Chapter Two takes up the representation of "infidels," which was a central theme in gazi lore, and which provides important clues into the ways frontiersmen identified themselves by identifying others. Chapter Three looks at the representation of other Turco-Muslim polities in connection with the Ottoman search for a self-identity and hence with an increasing interest in the political legacy of the steppe tradition. Finally, Chapter Four discusses resistance to state centralization which is articulated by reactions to the neglect of gaza and to the adoption of Istanbul as the new seat of power.
Keywords: Epic literature, Turkish.